Targeted delivery of autoantigen to dendritic cells prevents development of spontaneous uveitis - Klaska, Izabela P.; Yu, Tian; Fordyce, Rosie; Kamoi, Koju; Cornall, Richard J.; Martin-Granados, Cristina; Kuffova, Lucia; Forrester, John V. (Frontiers in Immunology, 2023)
DEC205, dendritic cells, fusion protein, autoimmune, uveitis, hen egg lysozyme IntroductionUveitis is a major source of visual impairment accounting for up to 10% of all causes of blindness (1, 2). Infectious agents account for a significant proportion of cases but in a majority of patients no specific cause can be identified (3). Such cases are currently described as "undifferentiated" uveitis (4) although latent or persistent infection may be lurking undetected (5). Autoimmune/autoinflammatory processes are considered to play a role in many cases of undifferentiated uveitis, concepts based on experimental models of uveitis induced by retina-specific antigens (6). This has been supported by the generation of a transgenic T cell receptor (TCR) mouse model of spontaneous experimental autoimmune uveitis/uveoretinitis (EAU), in which 30% of pathogenic T cells are specific for the retinal protein interphotoreceptor retinol binding protein (IRBP), underscoring a role for an autoimmune pathogenesis in this disease (7).We have developed a model of spontaneous EAU, in which the neoantigen hen egg lysozyme (HEL) is expressed in the retina under control of the IRBP promoter (8). When single transgenic IRBP-HEL mice (sTg HEL mice) are crossed to mice expressing a transgenic T cell receptor (TCR) for HEL (sTg TCR mice), double transgenic mice (dTg IRBP:HEL TCR mice, hereafter termed dTg mice) spontaneously develop EAU with onset around post-natal day (P)20/21 and with 100% incidence. Inflammation progressively worsens to reach a peak at P30 and eventually leads to total retinal destruction, with phthisis bulbi (ocular shrinkage) occurring in some mice (9). The